PENDEKATAN NON FORMAL DAN FORMAL DALAM MENGANALISIS ARTEFAK SEBAGAI MEDIA PENDIDIKAN SEN1 RUPA - Iswahyudi Iswahyudi; Mardiyatmo Mardiyatmo (Jurnal Cakrawala Pendidikan, 1999)
An artifact is an object made by man and assumedto possess symbolic and esthetic values. An artifactcomes into existence through a concept of creationand based on an esthetic aspect.Artifacts can be used as educational media forcertain teaching materials. They can be in the form ofhardware (e.g., temples) and software (e.g., paintings).Non formal and formal approaches can be usedto analyze artifacts so that a comprehensive understandingis obtained. Such a combined use of approaches isalso multidimensional and structural in nature so thatorigins and developments can be found.